PENINGKATAN WAWASAN KEBHINEKAAN MELALUI PENGGUNAAN VIDEO G-30S/PKI DI SANGGAR BELAJAR KAMPUNG BHARU - Khairani, Khairani; sari, Suci perwira (Universitas Muhammadiyah Makassar, 2025)
This study aims to enhance students' multicultural awareness through the use of the G-30S/PKI video as a learning medium. The research method used is classroom action research (CAR) with a quantitative approach. This research was conducted at Sanggar Belajar Kampung Bharu during the odd semester of the 2024/2025 academic year, involving 12 students as subjects. The research process was carried out in two cycles, each involving four stages: planning, implementation, observation, and reflection. Data collection techniques were conducted through questionnaires, multicultural awareness tests (pre-test and post-test), and observations. The questionnaire results showed positive responses from students with an average score of 91.42, classified as very good. In addition, the test results indicated an average increase in pre-test scores from 68.25 to 88.50 in the post-test, with an improvement percentage of 29.25%. These findings indicate that the G-30S/PKI video is effective as a learning medium in enhancing multicultural awareness. The use of video as a learning medium has been proven to increase learning interest and student engagement in understanding multicultural concepts more deeply. Thus, this study recommends using historical documentary videos as an innovative learning medium to enhance multicultural awareness and tolerance attitudes among students.